Hamiltonian-Based Approach to Enhance the Stability of Hybrid Fuel Cell and Supercapacitor Sources - Pongsiri Mungporn; Uthen Kamnarn; Burin Yodwong; Surin Khomfoi; Serge Pierfederici; Babak Nahid-Mobarakeh; Gianpaolo Vitale; Nicu Bizon; Phatiphat Thounthong (IEEE Open Journal of Industry Applications)
This article aims to study an improved large-signal stability for fuel cell (FC) and supercapacitor (SC) hybrid sources, employing the enhanced Hamiltonian control law. This novel approach addresses the inherent challenges in the dynamic operation of such hybrid systems, characterized by rapid load changes [i.e., constant power load (CPL)] and energy fluctuations. Grounded in energy-based control theory, the Hamiltonian control law accurately manages the energy exchange between the FC, SC, and external load aiming to improve system stability and response efficiency. A comprehensive test bench setup, including a real FC, an SC bank, and programmable loads to simulate the electrical load (i.e., CPL, constant resistive load, and constant current load), was developed to evaluate performance under various operational conditions. The results demonstrate that Hamiltonian-based control significantly enhances the system’s damping properties, ensuring a smoother response to load variations and enhanced stability across different scenarios.